Ultrasound as a Sole Diagnostic Modality for Diagnosis of Acute Appendicitis-an Experience from Tertiary Care Hospital - Faryal Eid, Ayesha Khan Afridi, Sana Urooj, Usba Jamil, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute appendicitis is among the most frequent causes of acute abdominal pain that necessitates emergency surgery both internationally and in our country. Ultrasound is a readily available diagnostic modality, however with advancement in its resolution power and technological advancements, its diagnostic accuracy is improving with every passing year. Objective: To evaluate the diagnostic accuracy of ultrasound in diagnosis of acute appendicitis Methodology: This descriptive cross sectional study was carried out in the Surgery department of Khyber Teaching Hospital, Peshawar from 20/6/2020 to 20/12/2020. A total of 165 patients presenting with acute appendicitis with duration of symptoms 1-2 days, patients in age between 18-65 years and both gender (male/female) were included. A detail history, clinical examination and routine laboratory investigations were performed as per study protocol. All the included patients were referred to radiology department for ultrasound for the diagnosis of acute appendicitis. Acute appendicitis on ultrasound was labeled as positive or negative according to criteria defined in operational definition. After surgery the specimen was sent to hospital laboratory for histopathology. Acute appendicitis on histopathology was labeled as positive or negative according to criteria defined in operational definition. Results: In the present study mean age was 41 years with SD ± 11.76. 91. Based on diagnostic accuracy of ultrasound, the sensitivity was 91.71%, specificity was 62.5%, PPV was 97.95%, NPV was 27.77% and the diagnostic accuracy was 90.30%. Conclusion: Our study concludes that ultrasound has the sensitivity of 91.71%, specificity 62.5%, PPV 97.95%, NPV 27.77% and the diagnostic accuracy was 90.30% in diagnosis of acute appendicitis. Keywords: diagnostic accuracy, ultrasound, acute appendicitis, histopathology,